P1270 Systolic blood pressure at age 40 is associated with left atrial volumes at age 64. (17th January 2020) - Selmer Roenningen, P; Berge, T; Solberg, M G; Enger, S; Nygaard, S; Pervez, O; Orstad, E B; Kvisvik, B A; Aagaard, E N; Lyngbakken, M N; Ariansen, I; Rosjo, H; et al.
Abstract: Funding Acknowledgements: Vestre Viken Hospital Trust Background: Left atrial (LA) enlargement is associated with elevated blood pressure (BP) and with cardiovascular morbidity and mortality. In the assessment of LA size, echocardiographic guidelines recommend the use of LA end-systolic volume (LAVmax). LA end-diastolic volume (LAVmin) and LA emptying fraction (LAEF) may add valuable information in risk assessment. The knowledge of early adulthood BP and its association to LA volumes and LAEF later in life is limited. Purpose: To explore the association between systolic BP at age 40 and LA volumes and LAEF at age 64. Methods: We linked data from subjects who had participated in both a nationwide cardiovascular screening survey (1990-1991) at the age of 40, and the Akershus Cardiac Examination (ACE) 1950 Study (2012-2015) at the age of 64 (n = 2, 597). In the ACE 1950 Study, LAVmax and LAVmin were measured with echocardiography according to the summation of discs method. LAEF was calculated as (LAVmax-LAVmin/LAVmax)x100%. The association between systolic BP at age 40 and LA volumes and LAEF at age 64 was assessed in univariate and multivariate linear regression analyses. Results: Systolic BP at age 40 was associated with LAVmax and LAVmin but not with LAEF at age 64. In our multivariate model, a 10 mm Hg higher systolic BP at age 40 was associated with a 0.9 ml greater LA end-systolic volume and a 0.5 ml greater LA end-diastolic volume at age 64. Conclusion: Early adulthood systolic BP is associated with LA volumes 24 years later in life.